The Relationship between Sleep Patterns and the Incidence of Dysmenorrhea in YARSI University Faculty of Medicine Students in 2020-2011 and the Review from an Islamic View - fetricia catherina; Zakiyah Zakiyah; Firman Arifandi (Junior Medical Journal, 2023)
Introduction: Dysmenorrhea is pain that is felt in the pelvic area due to menstruation and the production of prostaglandin substances. Dysmenorrhea is caused by many factors, one of which is sleep patterns. This study aims to find out whether there is a relationship between sleep patterns and the incidence of dysmenorrhea in YARSI University Medical Faculty Students Batch 2020-2021 and Reviews According to an Islamic View.Method: This type of research is correlational with a cross sectional approach and the method of determining the sample is purposive sampling. The sample in this study were YARSI University Medical Faculty Students Class of 2020-2021, a total of 97 students. Data collection was carried out using a questionnaire.Result: From the results of statistical analysis, it was found that 5 (5.2%) respondents with good sleep patterns experienced mild to moderate dysmenorrhea. While 92 (94.8%) of respondents with poor sleep patterns experienced mild dysmenorrhea as many as 46 (47.4%), moderate as many as 42 (43.3%) and severe as many as 4 (4.1%). The results of the Chi square test obtained a p value of 0.417 ( 0.05) which indicated that there was no significant relationship between sleep patterns and dysmenorrhea in YARSI University Faculty of Medicine Students class of 2020-2021.Conclusion: There is no significant relationship between sleep patterns and dysmenorrhea in YARSI University Faculty of Medicine Students class of 2020-2021. However, there is an increased risk of mild to moderate dysmenorrhea in respondents who have poor sleep quality.